Analysis of stability aspects of a large constant power load in a local grid - Romlie, M.F. (2013)
This paper investigate the problem of instability of constant power load (CPL) fed via a diode bridge rectifier connected in a local AC distribution system fed by wind farm with energy storage system installed. Analysis and simulation illustrates first that the instability as a function of the various system parameters, then control based solutions for improving the stability is proposed and verified by analytical method and simulation in PSCAD. Â© 2013 IEEE.